Antibacterial Activity of Green Meniran Extract (Phyllanthus niruri Linn) on The Growth of Salmonella typhimurium - Nafisah, Aulia Erta; Octavia, Bernadetta; Lestari, Endang Gati (Indonesian Journal of Bioscience (IJOBI), 2023)
Salmonella typhimuriumis a bacterium that causes digestive infections, gastroenteritis, and food poisoning, psickcaused byBacterial infection is a health problem in developing countries, including Indonesia. Green meniran (Phyllanthus niruri L.), is a herbaceous plant containing flavonoids, alkaloids, saponins, and tannins which have antibacterial activity which is expected to suppress the development of Salmonella sp. The aim of the study was to determine the ability of green meniran extract as an antibacterial to inhibit the growth of Salmonella typhimurium bacteria. The study used a completely randomized factorial design consisting of two factors, namely extract concentrations of 5%, 10%, 20%, 40%, 80%, equipped with a positive control (chloramphenicol) and negative control (aquades), as well as the age of the inoculum of the bacterial growth phase. Testing the antibacterial activity using the Kirby-Bauer disc diffusion method. The results showed that green meniran extract had antibacterial activity against the growth of Salmonella typhimurium bacteria. Concentrations of 5%, 10%, 20%, 40%, and 80% produced inhibition zone diameters of 6.7 mm, 8.5 mm, 9.9 mm, 12 mm, and 14.6 mm, respectively. The concentration of 80% green meniran extract is effective in inhibiting the growth of Salmonella typhimurium bacteria with an antibacterial effectiveness value of 58.95%.